Pengaruh Kualitas Pelayanan dan Harga terhadap Minat Beli Telkomsel By.U - Bimo Muhammad Widono; Donant Alananto Iskandar (UNIVERSITAS KALBIS, 2022)
This study aims to analyze the effect of service quality and price on buying interest in Telkomsel by u. Determination of the sample in this study using a non-probability sampling technique with purposive sampling method with a sample of 180 students at Kalbis Institute. The data analysis technique used is multiple linear regression analysis and t test. The results of the t test show that the service quality variable is 10.062 > t table (1.976) which means that the service quality variable partially affects buying interest and the price is -0.0271 < t table (1.976) which shows that partially the price variable has no significant effect on interest in buying Telkomsel by u.